Factors related to work-related stress among pharmacists in the south of Jordan - Alnawaiseh, Nedal Awad; Al-Kubaisy, Waqar; A-lkubaisi, Omar Waseem; Alnawayseh, Nashat Abdel Rahim; Eddin, Sadeen Zein; Alqaisi, Rashed (Journal of the Pakistan Medical Association, 2025)
Objective: To identify the prevalence of and risk factors associated with work-related stress among pharmacists. Method: The cross-sectional study was conducted from January 3 to July 1, 2022, in the Alkarak Governorate of Jordan after approval from the ethics review committee of Mutah University, Jordan. The sample comprised qualified pharmacists with at least one year of professional experience. Data was collected using a validated and reliable self-administered questionnaire containing 20 items under five main domains. Each item was scored on a 5-point Likert scale. Data was analysed using SPSS 25. Results: Of the 179 pharmacists with mean age 32.5±7.7 years and mean professional experience 7.7±6.3 years, 122(68.2%) were females and 57(31.8%) were males. Of the total, 145(81%) pharmacists demonstrated moderate work-related stress, while 4(2.2%) showed a high level. Gender, working hours per week, number of prescriptions dispensed per day, number of pharmacists per shift, employment status, and years of professional experience were significantly associated with the level of work-related stress (p<0.05). Conclusion: Several factors were found to have a significant relationship with work-related stress among pharmacists. Key Words: Work-related Stress, Pharmacists, Risk factor, Gender, Years of experience.